Influência da tensão elétrica na transferência por curto circuito na soldagem GMAW do aço carbono - FERREIRA, Thaíres Vieira (2022)
In order to perform a quality weld, it is necessary that the process be stable, which happens when there is regularity in the metallic transfer, amount of spatter generated and aspects of the weld bead. In short-circuit transfer, the stability of the process is directly affected by the periodic arc extinctions, which occur when the transferred metallic drop comes into contact with the weld pool. This characteristic favors an increase in the generation of spatter, which reduces the productive capacity of the process, either due to the loss of filler material or the need to spend on removal, in addition to affecting the final quality of the weld. In this context, it is proposed to evaluate the regularity of short-circuit transfer during welding by simple deposition on AISI 1020 steel plates with AWS ER 70S-6 wire, correlating them with the Vilarinho Regularity Index for Transfer in Short Mode -Circuit (IVcc), the geometric regularity and surface finish of the weld beads. Therefore, it was decided to vary the voltage between 19 and 24 V, keeping the other parameters fixed and CO2 as the shielding gas. The results indicated a good range of regularity, among the analyzed values, for voltages from 20 to 22 V, as well as surface quality of the beads and a lower level of spatter.